Reticular formation responses to magnetic brain stimulation of primary motor cortex - Fisher, Karen M.; Zaaimi, Boubker; Baker, Stuart N. (The Journal of physiology, 2012)
Key points • Transcranial magnetic stimulation (TMS) is a popular technique for the non‐invasive investigation of motor function and is often assumed to influence spinal circuits solely via the corticospinal tract. • In anaesthetized monkeys, we observed robust responses to TMS over motor cortex in single units recorded within the brainstem reticular formation. • Short latency responses were consistent with activation of a cortico‐reticular pathway. More powerful later responses seemed to be associated with the click sound produced by the coil on discharge. • Activation of brainstem neurones by sound must be considered as a potential confound during future TMS studies. • TMS might provide an easy, non‐invasive method for activating the motor reticular formation in human subjects. Transcranial magnetic stimulation (TMS) of cerebral cortex is a popular technique for the non‐invasive investigation of motor function. TMS is often assumed to influence spinal circuits solely via the corticospinal tract. We were interested in possible trans‐synaptic effects of cortical TMS on the ponto‐medullary reticular formation in the brainstem, which is the source of the reticulospinal tract and could also generate spinal motor output. We recorded from 210 single units in the reticular formation of three anaesthetized macaque monkeys whilst TMS was performed over primary motor cortex. Short latency responses were observed consistent with activation of a cortico‐reticular pathway. However, we also demonstrated surprisingly powerful responses at longer latency, which often appeared at lower threshold than the earlier effects. These late responses seemed to be generated partly as a consequence of the sound click made by coil discharge, and changed little with coil location. This novel finding has implications for the design of future studies using TMS, as well as suggesting a means of non‐invasively probing an otherwise inaccessible important motor centre.